Antibody-drug conjugates in cancer therapy: current advances and prospects for breakthroughs - Wu, Dan; Yang, Kaixuan; He, Runjia; Yin, Rutie; Shui, Lin (Frontiers in Cell and Developmental Biology, 2025)
Antibody-drug conjugates (ADCs), often referred to as “intelligent biological missiles,” have garnered significant attention in the rapidly evolving landscape of cancer therapy. ADCs represent a sophisticated approach by integrating monoclonal antibodies (mAbs), which are particular targeting tumor antigens, with cytotoxic payloads, which deliver lethal effects. Compared with the combination of chemotherapy and mAbs, ADCs precisely deliver highly potent cytotoxins directly to tumor cells while minimizing damage to healthy tissues. However, limitations such as significant adverse effects, suboptimal therapeutic efficacy, and drug resistance require carefully evaluation and further optimization. Further studies are necessary to explore the next-generation of ADCs, such as the combination of ADCs with other anti-tumor strategies, bispecific ADCs, dual-payload ADCs and radionuclide drug conjugates (RDCs). This review provides a comprehensive overview of recent developments in oncology treatment, focusing on the historical evolution, structural design, clinical advancements, and mechanisms of action of approved ADCs. Each structural element, including the target antigen, mAb, linker system, and cytotoxic payload, as well as advancements in payload conjugation technology, plays a critical role in the development of ADCs. Through ongoing refinement and innovation, it is anticipated that next-generation ADCs with enhanced therapeutic benefits for patient populations can be realized.